AWS for Admins - John Paul Mueller (Wiley, 2017)
Amazon Web Services (or AWS) has grabbed the attention of the business world—in more ways than one. If you just want to manage administrative tasks with AWS, your goal is to figure out what you need and create a basic, functional setup that lets you become productive as quickly as possible. This guide cuts through all the hype and clutter to get you where you need to go. With simple procedures you can follow to set up and configure the right environment, it helps you assess your move to the cloud, explains any quirks in the software, and gets you up and running.